Organizational justice and quality of work life in hotels: The mediating effect of trust climate - Akter, Kaniz Marium; Tang, Swee Mei; Adnan , Zurina (Society & Sustainability, 2023)
The study aimed to investigate the impact of hotels’ organizational justice (OJ) on the quality of employees’ work life (QWL), with the mediation effect of teams’ climate of trust (CT). Social Exchange Theory was employed to support the research framework. Data were collected using 281 questionnaires from the operational employees of 3-star hotels in Bangladesh and assessed by SPSS version 21 and SmartPLS 3.0 software. Data were validated by a measurement model and hypotheses were tested by a structural model using the PLS-SEM approach. The study discovered significant effects of hotels’ organizational justice (β=0.271) and team’s climate of trust (β=0.362) on employees’ quality of work life (R2=27.7%). It also reveals the effect of the hotel’s OJ (β=0.369) on teams’ CT (R2=13.6%), and a partial mediation effect of team’s CT (β=0.134) in the relationship between the hotel’s OJ and employees’ QWL. Results indicate that hotels’ organizational justice practices enrich employees’ quality of work life and nurture mutual trust among the team members, while a team’s climate of trust can convert hotels’ organizational justice into employees’ quality of work life. These findings would inspire the hotel authorities in practicing organizational justice to develop a trusting climate in the working teams, and designing QWL programs for attaining employee satisfaction. The study was limited to the Bangladesh hotel industry which restricts the generalizability of its results.